К вопросу о жизнедеятельности комплекса – человек, система, среда - Драганов, Б. Х.; Масюк, Н. Ю. (Energy and Automation, 2017)
UDC 697.11 TO THE PROBLEM OF LIFE COMPLEX - PEOPLE, systems, environments B. Draganov, N. Masuk Subject of research - the basis of life support: people, systems, environments. The purpose of research - to develop a method to ensure comfortable conditions Complex life support - the person, the system, the environment. Materials and methods of research. providing vital functions of the operator system is the formation of the desired environment, taking into account the mutual work of the operator environment and possibly other systems in the conditions of complex influence of extreme factors. However, some factors are deterministic, stochastic other. In real time, rapidly developing new scientific and technical direction - ergonomics, which is intended to serve the complex operator - system - Wednesday. The complex operator, technical system, the environment should be provided with conditions for compatibility. Information compatibility is to create an information model, an adequate system. Biophysical compatibility operator system and environment is to achieve a reasonable compromise between the workability and physiological condition of the operator. Spatially anthropometric compatibility operator and the machine is that based on anthropometric characteristics and some physiological characteristics of the operator (dynamic anthropometry) and the conditions dictated by the particular task required to create jobs. The results of research. Any sub-system shall comply with the operational requirements of a technical device. Harmful impurities contained in the air at concentrations that do not exceed the permissible predel¬no have nonspecific effects on the human body. The simultaneous presence of several substances in the air can lead to amplification of nonspecific action effect. As a growing number of technical means, we are increasingly confronted with cases where the person is unable to fully use their potential. However, one can not overestimate the possibilities of complex systems. Currently, a complex machine, the technical system and the person for whom it is created, it is already impossible to consider separately. The system design should ensure the preservation of physical, chemical and sanitary characteristics. The essential issue is the compatibility of the biophysical operator system environment. Thermal indoor climate and human body heat production interdependent factors, and this problem affects attention. When the physical load exceeds the capacity of man, the developing state of exhaustion even in the case provided for this work neob¬hodimoe oxygen. The oxidation process occurring in the human body by Fanger theory, consist of external mechanical work and heat requirement inside (N). Skin temperature can be taken as one of the characteristics teplooschuscheniya. Thermal sensation person closely associated with the heat transfer of his body. When calculating the thermal sensation to explorer task, given the heat production of the human body, as well as the clothes and the type of work to determine the technical parameters, fits nicely teplooschuscheniyu most people. Сonclusions At the present time there is a significant development of the scientific and technological system in all areas of production. To ensure effective systems of life people - the technical installation - the environment and the formation of habitat necessary to the implementation of relevant studies and an article dedicated to this task - the basic conditions and is a parameter calculation method corresponding to a comfortable feeling.